2015
DOI: 10.4028/www.scientific.net/ssp.242.135
|View full text |Cite
|
Sign up to set email alerts
|

Vacancy Species Produced by Rapid Thermal Annealing of Silicon Wafers

Abstract: Rapid thermal annealing (RTA) of Czochralski silicon wafers at around 1260°C installs a depth profile of some vacancy species. Subsequent oxygen precipitation in such wafers is vacancy-assisted. The data on RTA-installed vacancy profiles - and the corresponding precipitate density profiles - suggest that there is a slow-diffusing vacancy species (Vs) along with two fast-diffusing species: a Watkins vacancy (Vw) manifested in irradiation experiments and fast vacancy (Vf) responsible for the high-T vacancy contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Although the present analysis assumed a single kind of V, the concept of several quasi‐independent forms of a free vacancy cannot be dismissed altogether. The monitored vacancy in RTA wafers seems to disappear by conversion into a faster vacancy form (denoted V f ) with subsequent quick out‐diffusion of V f to the wafer surface . This additional loss channel of V + V* (apart from their own out‐diffusion and recombination with self‐interstitials) is not manifested in the presently discussed donor profiles.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Although the present analysis assumed a single kind of V, the concept of several quasi‐independent forms of a free vacancy cannot be dismissed altogether. The monitored vacancy in RTA wafers seems to disappear by conversion into a faster vacancy form (denoted V f ) with subsequent quick out‐diffusion of V f to the wafer surface . This additional loss channel of V + V* (apart from their own out‐diffusion and recombination with self‐interstitials) is not manifested in the presently discussed donor profiles.…”
Section: Discussionmentioning
confidence: 84%
“…The apparent vacancy diffusivity D deduced by various techniques in silicon wafers is systematically smaller than the expected free vacancy diffusivity, and the values of D seem to be random. Previously, it was suggested that a vacancy can exist in several structural forms, of strongly different diffusivities (slow forms and fast forms), with a relatively slow exchange between these forms. Different kinds of vacancy (or a mixture of them) can be manifested depending on the experimental conditions, for different time scales of observation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several models have been proposed to describe vacancy‐related defect profiles after various thermal treatments. Thus, oxygen precipitation profiles after RTA annealing at 1250 °C with different ramp down rates can be described by a simple vacancy and self interstitial diffusion and recombination , while changes in such defect profiles during the subsequent anneals at 1000 °C temperature range require an introduction of vacancy agglomeration , or most recently, the introduction of multiple vacancy species with different diffusivities . Most of the models agree that the vacancies bind to oxygen atoms and exist predominantly in the form of VO 2 complexes at room temperature.…”
Section: Introductionmentioning
confidence: 98%